Assessment of salivary and plaque pH and oral health status among children with and without intellectual disabilities - G Radha; V Swathi; Abhishek Jha (Wolters Kluwer Medknow Publications, 2016)
Background: This study explores the association of disabilities and oral health. The aim of the study was to assess the salivary and plaque pH and oral health status of children with and without disabilities. Materials and Methods: A total of 100 schoolchildren (50 with disabilities and 50 without disabilities) were examined from 9 to 15 years age group. Saliva and plaque pH analysis were done to both the groups. Clinical data were collected on periodontal status, dental caries using WHO criteria. pH values of different groups, difference between the means were calculated using independent t-test, and frequency distribution was analyzed using Chi-square test. Statistical significance, P value was set at 0.05. Results: Mean plaque and salivary pH scores were lesser (5.73 and 5.67) in children with intellectual disabilities (IDs) (P< 0.001). Subjects with disabilities had also statistically significant higher CPI scores and decayed, missing, and filled scores than their healthy counterparts (P< 0.001). Conclusion: There is a statistically significant difference in plaque and salivary pH among children with and without ID with lower plaque and salivary pH among children with ID. In addition to this, the oral health was also more compromised in children with ID, which confirms a need for preventive treatment for these children.